Structurally diverse diterpenoids from Isodon pharicus. Issue 15 (6th July 2018) - Hu, Zheng-Xi; Xu, Hou-Chao; Hu, Kun; Liu, Miao; Li, Xiao-Nian; Li, Xing-Ren; Du, Xue; Zhang, Yong-Hui; Puno, Pema-Tenzin; Sun, Han-Dong
Abstract : Twenty-one structurally diverse diterpenoids (1–21 ), wherein1, 2, and4 represented unprecedented architectures, were isolated from Isodon pharicus . Abstract : Twenty-one diterpenoids with diverse structures, including twelve new compounds (1–12 ), were isolated from the aerial parts of Isodon pharicus . Structurally, pharicusin A (1 ), composed of a benzoyl group coupled to a 7α, 20-epoxy- ent -kauranoid, represents an unprecedented C27 meroditerpenoid; pharicusin B (2 ) is a novel trinorditerpenoid with an unreported 15, 16, 17-trinor-7α, 20-epoxy- ent -kaurane skeleton; pharicusin C (4 ) represents the first example of 7α, 20-epoxy- ent -atisane diterpenoids. Their structures were elucidated based on spectroscopic analysis, wherein the absolute configurations of2 and3 were further confirmed by single-crystal X-ray diffraction and computational analysis of the optical rotatory dispersion (ORD). Selected sixteen isolates were evaluated for their in vitro cytotoxicity against a small panel of human tumor cell lines (HL-60, SMMC-7721, A-549, MCF-7, and SW-480), and compounds9, 10, 13, 16, and18 exhibited significant inhibitory effects against all five cell lines, with IC50 values in the range of 0.37–6.03 μM.